An annotated catalogue of the gamasid mites associated with small mammals in Asiatic Russia. The family Haemogamasidae (Acari: Mesostigmata: Gamasina) - Vinarski, Maxim V.; Korallo-Vinarskaya, Natalia P. (Zootaxa, 2017)
We provide a list of the species of the family Haemogamasidae Oudemans, 1926 living in Asiatic Russia, with data on their synonymy, distribution, and relationships with mammal hosts. In total, 23 species of mites distributed between two genera (Eulaelaps Berlese, 1903, and Haemogamasus Berlese, 1889) are covered.